2018
DOI: 10.3390/catal8040140
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Atomic-Level Understanding of Cu/SSZ-13 Selective Catalytic Reduction Catalysts

Abstract: Cu/SSZ-13 Selective Catalytic Reduction (SCR) catalysts have been extensively studied for the past five-plus years. New and exciting fundamental and applied science has appeared in the literature quite frequently over this time. In this short review, a few topics specifically focused on a molecular-level understanding of this catalyst are summarized: (1) The nature of the active sites and, in particular, their transformations under varying reaction conditions that include dehydration, the presence of the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 59 publications
5
94
0
Order By: Relevance
“…Amongst state-of-the-art metal-promoted zeolite catalysts used in this process, Cu-exchanged chabazite (Cu-CHA) shows excellent activity and extraordinary hydrothermal stability over a broad temperature range under SCR conditions, triggering intensive research on the relationship between its unique structure and its DeNO x performance [3][4][5][6][7][8][9][10][11]. In this regard, the SiO 2 /Al 2 O 3 ratio (SAR) and the Cu loading content are important structure indexes, which could affect the nature of Cu cations existing in the catalyst framework and, based on their nature, location and redox properties, further impact the SCR activity [3][4][5][6][7][8][9]. Two Cu species are recognized to be present in the Cu-CHA catalyst: Z 2 Cu II (doubly coordinated to the framework) and ZCu II OH (balanced by one framework negative charge), whose relative ratio can be predicted based on Si/Al and Cu/Al ratios [5,6,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst state-of-the-art metal-promoted zeolite catalysts used in this process, Cu-exchanged chabazite (Cu-CHA) shows excellent activity and extraordinary hydrothermal stability over a broad temperature range under SCR conditions, triggering intensive research on the relationship between its unique structure and its DeNO x performance [3][4][5][6][7][8][9][10][11]. In this regard, the SiO 2 /Al 2 O 3 ratio (SAR) and the Cu loading content are important structure indexes, which could affect the nature of Cu cations existing in the catalyst framework and, based on their nature, location and redox properties, further impact the SCR activity [3][4][5][6][7][8][9]. Two Cu species are recognized to be present in the Cu-CHA catalyst: Z 2 Cu II (doubly coordinated to the framework) and ZCu II OH (balanced by one framework negative charge), whose relative ratio can be predicted based on Si/Al and Cu/Al ratios [5,6,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the SiO 2 /Al 2 O 3 ratio (SAR) and the Cu loading content are important structure indexes, which could affect the nature of Cu cations existing in the catalyst framework and, based on their nature, location and redox properties, further impact the SCR activity [3][4][5][6][7][8][9]. Two Cu species are recognized to be present in the Cu-CHA catalyst: Z 2 Cu II (doubly coordinated to the framework) and ZCu II OH (balanced by one framework negative charge), whose relative ratio can be predicted based on Si/Al and Cu/Al ratios [5,6,11]. The proportion of such Cu species could also be affected by several factors, for example, hydrothermal aging [4,6,12] or hydrated/dehydrated conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the zeolite framework, Cu species are also studied intensively. As commonly accepted, isolated Cu 2+ ions are the best catalytic active sites; CuAl 2 O 4 species are inactive in the reaction; other species such as [Cu(OH)] + -Z and [Cu-O-Cu] 2+ are still in debate [2,[15][16][17][18]. Gao et al [19] observed NH 3 oxidation followed [Cu-O-Cu] 2+ species formation under high levels of Cu ion-exchange degree.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the extent to which the NO conversion decreased after SO 2 introduction in the feed was relatively slight at 20 • C even if the catalyst did not regain its initial activity when SO 2 was removed, probably due to the formation of sulfates covering the active sites of the catalysts. The fourth article by Feng Gao et al (2018) [6] was devoted to the recent progress in atomic-level understanding of Cu/SSZ-13 selective catalytic reduction catalysts currently on the market for the control of NOx emissions from diesel vehicles. More specifically, the review focused on recent advances in the nature of catalytically active copper species, some limiting reactions involved in the SCR mechanism, and the effects of copper speciation on catalyst stability.…”
mentioning
confidence: 99%